Biology and Control of the Giant Red Bug Lohita grandis Gray (Hemiptera : Pyrrhocoridae : Largidae) - Joshi, K. C.; Khan, H. R. (Indian Forester, 1990)
Tbe giant red bug, Lohita grandis Gray is a pest of Trewia nudiflora, Bombax ceiba, Gossypium herbaceum etc in the warm humid forest areas of North-east India. The female develops quicker than male.There are four overlapping generations of the pest. The chemical control experiments were conducted to test the relative toxicity of insecticides so as to check the damage in young plantation. Hence ten modern insecticides i. e., Carbaryl, Dursban, Dichlorvos,Dimethoate, DDT, Endosulfan, Fenitrothion, Monocrotophos. M-parathion and Chloropyriphos were tested. The result showed that Carbaryl is the most effective and 39 15 times more toxic than DDT. The insecticide next to Carbaryl in toxicity waS found Chloropyriphos.